LOX-1 activation by oxLDL triggers an epithelial mesenchymal transition and promotes tumorigenic potential in prostate cancer cells. (1st February 2018) - González-Chavarría, I.; Fernandez, E.; Gutierrez, N.; González-Horta, E.E.; Sandoval, F.; Cifuentes, P.; Castillo, C.; Cerro, R.; Sanchez, O.; Toledo, Jorge R.
Abstract: Obesity is related to an increased risk of developing prostate cancer with high malignancy stages or metastasis. Recent results demonstrated that LOX-1, a receptor associated with obesity and atherosclerosis, is overexpressed in advanced and metastatic prostate cancer. Furthermore, high levels of oxLDL, the main ligand for LOX-1, have been found in patients with advanced prostate cancer. However, the role of LOX-1 in prostate cancer has not been unraveled completely yet. Here, we show that LOX-1 is overexpressed in prostate cancer cells and its activation by oxLDL promotes an epithelial to mesenchymal transition, through of lowered expression of epithelial markers (E-cadherin and plakoglobin) and an increased expression of mesenchymal markers (vimentin, N-cadherin, snail, slug, MMP-2 and MMP-9). Consequently, LOX-1 activation by oxLDL promotes actin cytoskeleton restructuration and MMP-2 and MMP-9 activity inducing prostate cancer cell invasion and migration. Additionally, LOX-1 increased the tumorigenic potential of prostate cancer cells and its expression was necessary for tumor growth in nude mice. In conclusion, our results suggest that oxLDL/LOX-1 could be ones of mechanisms that explain why obese patients with prostate cancer have an accelerated tumor progression and a greater probability of developing metastasis. Highlights: The Lectin-like oxidized LDL receptor 1, LOX-1 is overexpressed in prostate cancer and its expression is associated with high Gleason score. The activation of LOX-1 by oxLDL promotes an epithelial to mesenchyme transition, migration and invasion in prostate cancer cells. The activation of LOX-1 enhances tumorigenic potential and its expression is necessary for tumor growth of prostate cancer cells.